Web Deteksi Gangguan Kecemasan dan Depresi - Nina Sevani; Silvia Silvia (Ultimatics : Jurnal Teknik Informatika, 2015)
One of mental disorders that is often experienced by the population in Indonesia is anxiety and depression. Those disorders can interfere the activity if they are not handled properly. However, the lack of public knowledge of the symptoms of anxiety and depression, as well as the reluctance to consult a psychologist, can make the handling becomes too late. This problem can be overcome with the webbased application to detect anxiety and depression in the public. This application is made through several stages that begin with the literature study, interviews with psychologists, analyzing the needs of both application and database. The evaluation of this application is done by distributing questionnaires to 45 respondents who have tried to use this application, as well as functional and validity testing by psychologists. The results of the evaluation states that every feature in this application is functioning well, is easy to use and in accordance with the code of ethics of psychology.